Features of constructing data transmission systems over free-space optical routes - Kukhtin, S.M.; Fedorenko, E.P. (Radiotekhnika, 2025)
This paper provides an overview related to the current state of free-space optics systems, areas of their application and advantages compared to wireless radio-frequency systems. A review related to development history of such systems is also provided. Principles of transmitting/receiving equipment development, including common schemes, radiation sources, detectors and other basic components of these systems are covered in this paper. Analysis of the atmospheric conditions effect on optical signal transmission, such as atmospheric absorption, scattering and turbulence has been studied. The most common methods used to improve the efficiency of free-space optics systems are also considered in this paper.